Model Komunikasi Kelompok dalam Aktivitas Kerja Nelayan (Studi Kasus Kelompok Nelayan Ikan Terbang Galesong): Model of Communication Group - mustafa, Dalvi; arif, andi adri; Fachry, Mardiana (2339-1324, 2025)
This study aims to determine the group communication model that occurs in the activities of flying fish fishermen as the basis of work patterns and is still maintained until now. The basic method in this study is a descriptive analytical method with a qualitative approach, while the strategy used is a case study. This study was conducted in Bontomarannu Village, South Galesong District as one of the areas of flying fish fishermen groups that still use traditional methods. The determination of informants was carried out by snowball sampling where there were 35 informants used in this study. The results of this study indicate that the communication model that is built is still traditional as a hereditary force maintained between the bosses (punggawa) and the fishermen members (ABK) to be able to carry out flying fish fishing activities effectively and efficiently. The languages ​​used also still rely on the cultural heritage of ancestors who are believed to be able to get maximum catches. the communication channels in the sawi fisherman work group are entirely with the land fisherman, where the land fisherman is the capital owner who has full authority in carrying out the work, by implementing a one-way communication system directly to its members, and only laborers or sawi fishermen carry out two-way communication in carrying out the work, to create better cooperation in the fishing process. Keyword: Fishermen, Working Activities, Communication